PENGARUH PEMBERIAN PACLOBUTRAZOL TERHADAP PERTUMBUHAN BANGLE (Zingiber purpureum Roxb) DALAM PENYIMPANAN IN –VITRO - Meynarti Sari Dewi Ibrahim (Buletin Penelitian Tanaman Rempah dan Obat, 2005)
Effect of Paclobutrazol On The Growth of In Vitro Concerved Purple Ginger (Zingiber purpureum Roxb)Effect of paclobutrazol on the growth of Purple Ginger (Zingiber purpureum  Roxburgh) conserved in vitro were studied in the Laboratory of Breeding and gremplasm of Indonesian Spice and Medicinal Crops Research Instituted, from February to November 2003. Sterile shoots of Purple Ginger were used as explants sources. The treatments evaluated were paclobutrazol 0 (control); 1; 2; 3 mg/l and arranged in completely randomized design with 10 replications. The aim of research was to study the effect of paclobutrazol on the growth of Purple Ginger conserved in vitro.  Results showed that at 5 months of culture age, paclobutrazol significantly reduced the number of shoots, height number of leaves and number of roots. The higher the concentration of paclobutrazol, the lower the number of shoots, leaves and roots and the shorter the root of plantlets observed. Application of paclobutrazol at concentration of 2 or 3 mg/l could prolong the conservation period up to 9 months. Fur there more it was revealed that paclobutrazol application produced more vigorous plantlets.